Lawrence-Seip syndrome. - Miteva, L.; Nikolova, A. (European Journal of Pediatric Dermatology, 2000)
A case of congenital total lipodystrophy (Lawrence-Seip syndrome) in 15-year old girl is reported. The patient had acanthosis nigricans, generalized lipoatrophy, hernia, hypertrophic clitoris and hypoplastic uterus, hirsutism, hepatomegaly with fatty liver, hyperlipidemia and hyperglycemia with insulin resistance. We have reviewed the reported cases of lipodystrophy and acanthosis nigricancs and discussed the characteristics of their association.